2018
DOI: 10.1002/asi.24118
|View full text |Cite
|
Sign up to set email alerts
|

The dominant factor of social tags for users’ decision behavior on e‐commerce websites: Color or text

Abstract: Colored Tags (abbr.Tag) as a unique type of social tags is used on e‐commerce websites (e.g., Taobao) to summarize the high‐frequency keywords extracted from users' online reviews about products they bought before. Tag is represented inked red or green according to users' personal experiences and judgments about purchased items: red for positive comments, green for negative ones. The valence of users' emotion induced by red or green is controversial. This study firstly discovers that colored tags inked in red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Barton et al 68 found that brightness has a significant effect on sensitivity, and high brightness areas can attract more attention. When red is used as a disturbing factor, the target's attention will be distracted 38 . However, when red is the target factor, its attention capture is magnified 69 …”
Section: Discussionmentioning
confidence: 99%
“…Barton et al 68 found that brightness has a significant effect on sensitivity, and high brightness areas can attract more attention. When red is used as a disturbing factor, the target's attention will be distracted 38 . However, when red is the target factor, its attention capture is magnified 69 …”
Section: Discussionmentioning
confidence: 99%
“…Another advantage is reflecting the tag content in the original format of the textual tag. In other words, regardless of the visualization method applied, the original word, language and writing format of the tag will not be changed (Xu and Zhang, 2018). The visualization of a tag does not affect the understanding of the original textual tag's meaning but helps to highlight certain tags that need to be specially noted to improve the efficiency of tag reading.…”
Section: Visualized Textual Tcsmentioning
confidence: 99%
“…Moreover, tags have also been exploited to solve other practical problems, such as interest discovery (Li, Guo, & Zhao, 2008; Yang, Song, & Ji, 2015) and friend recommendation (Feng, Zhang, Wang, & Zhang, 2014; Huang, Zhang, Wang, & Hua, 2015). On e‐commerce websites, tags have also been shown to have an impact on user decision‐making behavior (Xu & Zhang, 2019). However, there are some problems in the manual tagging mechanism.…”
Section: Introductionmentioning
confidence: 99%